Havana: space through tourism (2009)
Milton Santos, important Brazilian geographer, stated in his writings that space is a social production through time. The present work belongs to a series of studies of Latin-American cities based on Santos´ theories. Our case study is the city of Havana. Strategically situated in the Antilles, the city always played the role of a gate to the Spanish colonies in the Americas. After the Cuban independence (1898), the Caribbean city fell under the influence of the crescent power of the United States. At the turn of the XXth century, the city which during the colonial times based its economy on trade of commodities from the mainland like tobacco or sugar, turned to be funded mainly by North American tourism. The city attracted legal investment and mafia groups equally. Disparity and growing authoritarianism led to the well known Cuban Revolution and with its socialist reforms, the city froze in time. With the Soviet collapse, the government searched for economic alternatives facing a strong U.S. embargo. Tourism appeared once more as an important source of income. Yet, this new transition raises questions like: how is this reorientation going to change spatially Havana? Or, how are deeper changes in the socialist regime going to affect the heritage and identity of the city?